Perspectives of digestive pest control with proteinase inhibitors that mainly affect the trypsin-like activity of Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) - M.E. Pereira; F.A. Dörr; N.C. Peixoto; J.F. Lima-Garcia; F. Dörr; G.G. Brito (Brazilian Journal of Medical and Biological Research, 2005)
The present study describes the main characteristics of the proteolytic activities of the velvetbean caterpillar, Anticarsia gemmatalis Hübner, and their sensitivity to proteinase inhibitors and activators. Midguts of last instar larvae reared on an artificial diet were homogenized in 0.15 M NaCl and centrifuged at 14,000 g for 10 min at 4ºC and the supernatants were used in enzymatic assays at 30ºC, pH 10.0. Basal total proteolytic activity (azocasein hydrolysis) was 1.14 ± 0.15 absorbance variation min-1 mg protein-1, at 420 nm; basal trypsin-like activity (N-benzoyl-L-arginine-p-nitroanilide, BApNA, hydrolysis) was 0.217 ± 0.02 mmol p-nitroaniline min-1 mg protein-1. The maximum proteolytic activities were observed at pH 10.5 using azocasein and at pH 10.0 using BApNA, this pH being identical to the midgut pH of 10.0. The maximum trypsin-like activity occurred at 50ºC, a temperature that reduces enzyme stability to 80 and 60% of the original, when pre-incubated for 5 and 30 min, respectively. Phenylmethylsulfonyl fluoride inhibited the proteolytic activities with an IC50 of 0.39 mM for azocasein hydrolysis and of 1.35 mM for BApNA hydrolysis. Benzamidine inhibited the hydrolysis with an IC50 of 0.69 and 0.076 mM for azocasein and BApNA, respectively. The absence of cysteine-proteinases is indicated by the fact that 2-mercaptoethanol and L-cysteine did not increase the rate of azocasein hydrolysis. These results demonstrate the presence of serine-proteinases and the predominance of trypsin-like activity in the midgut of Lepidoptera insects, now also detected in A. gemmatalis, and suggest this enzyme as a major target for pest control based on disruption of protein metabolism using proteinase inhibitors.